2020
DOI: 10.3390/molecules25092170
|View full text |Cite
|
Sign up to set email alerts
|

Sigma-1 Receptor Positron Emission Tomography: A New Molecular Imaging Approach Using (S)-(−)-[18F]Fluspidine in Glioblastoma

Abstract: Glioblastoma multiforme (GBM) is the most devastating primary brain tumour characterised by infiltrative growth and resistance to therapies. According to recent research, the sigma-1 receptor (sig1R), an endoplasmic reticulum chaperone protein, is involved in signaling pathways assumed to control the proliferation of cancer cells and thus could serve as candidate for molecular characterisation of GBM. To test this hypothesis, we used the clinically applied sig1R-ligand (S)-(−)-[18F]fluspidine in imaging studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 69 publications
(89 reference statements)
0
4
0
Order By: Relevance
“…In a mouse model of glioblastoma multiforma, an increased σ 1 receptor density in the tumor was detected with ( S )-[ 18 F] 2 . An increased σ 1 receptor density was also observed during an autoradiographic analysis of samples from patients with glioblastoma using ( S )-[ 18 F] 2, confirming the translational relevance of σ 1 receptor imaging in oncology [ 59 ].…”
Section: Preclinical In Vivo Studies Of Racemic and Enantiomerically ...mentioning
confidence: 60%
See 1 more Smart Citation
“…In a mouse model of glioblastoma multiforma, an increased σ 1 receptor density in the tumor was detected with ( S )-[ 18 F] 2 . An increased σ 1 receptor density was also observed during an autoradiographic analysis of samples from patients with glioblastoma using ( S )-[ 18 F] 2, confirming the translational relevance of σ 1 receptor imaging in oncology [ 59 ].…”
Section: Preclinical In Vivo Studies Of Racemic and Enantiomerically ...mentioning
confidence: 60%
“… Fractions of unchanged PET tracer and radiometabolites in the plasma of various species determined at 30 and 60 min following intravenous administration of the corresponding radioligand [ 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ]. …”
Section: Figures Schemes and Tablesmentioning
confidence: 99%
“…administration of (S)-(−)-[ 18 F]fluspidine in the U87-MG tumor-bearing mouse model revealed the distribution of (S)-(−)-[ 18 F]fluspidine at early times and later times. 99 In another example, in a U87 intracranial GBM mouse model, they developed an ultrasmall, renal-clearable gold nanocluster intrinsically radiolabeled with 64 Cu ( 64 Cu-AuNCs-FC131) for targeted PET imaging of CXCR4 and showed the effective delivery of 64 Cu-AuNCs-FC131 into the tumors. Furthermore, at various dosages, in vivo toxicity studies revealed specific binding to U87 cells with no significant safety concerns, showing its potential as a useful platform for GBM imaging and drug delivery (Fig.…”
Section: Nanomedicines For Pet Imagingmentioning
confidence: 99%
“…MRI has low sensitivity but it provides the highest soft tissue contrast whereas CT provides low soft tissue contrast but it is fast compared to MRI. 99,104 PET has low spatial resolution but it is more sensitive compared to MRI. IR imaging has a very low depth of penetration but its sensitivity is high and it is fast.…”
Section: Nanomedicines For Multimodality Imagingmentioning
confidence: 99%